Pro-inflammatory Signaling in a 3D Organotypic Skin Model after Low LET Irradiation—NF-κB, COX-2 Activation, and Impact on Cell Differentiation - Acheva, Anna; Schettino, Giuseppe; Prise, Kevin M. (Frontiers in Immunology, 2017)
Nearly 85% of radiotherapy patients develop acute radiation dermatitis, which is an inflammatory reaction of the skin at the treatment field and in the surrounding area. The aims of this study were to unravel the mechanisms of radiation-induced inflammatory responses after localized irradiation in a human 3D organotypic skin culture model. This could provide possible inflammatory targets for reduction of skin side effects. 3D organotypic skin cultures were set up and locally irradiated with 225 kVp X-rays, using a combination of full exposure and partial shielding (50%) of the cultures. The secretion of pro-inflammatory cytokines, the phenotype and the differentiation markers expression of the cultures were assessed up to 10 days’ post irradiation. The pro-inflammatory transcription factor NF-κB (Nuclear Factor Kappa B) and COX-2 (Cyclooxygenase-2) pathways have been studied. The results showed fast activation of NF-κB, most likely triggered by DNA damage in the irradiated cells, followed by up-regulation of p38 MAPK and COX-2 in the irradiated and surrounding, non-irradiated, areas of the 3D cultures. The application of the COX-2 inhibitor sc-236 was effective at reducing the COX-2 mRNA levels 4 h post irradiation. The same inhibitor also suppressed the PGE2 secretion significantly 72 h after the treatment. The expression of a pro-inflammatory phenotype and abnormal differentiation markers of the cultures were also reduced. However, the use of an NF-κB inhibitor (Bay 11-7085) did not have the predicted positive effect on the cultures phenotype post-irradiation. Radiation-induced pro-inflammatory responses have been observed in the 3D skin model. The activated signaling pathways involved NF-κB transcription factor and its downstream target COX-2. Further experiments aiming to suppress the inflammatory response via specific inhibitors showed that COX-2 is a suitable target for reduction of the normal skin inflammatory responses at radiotherapy, while NF-κB inhibition had detrimental effects on the 3D skin model development.